Hybrid 5G optical‐wireless SDN‐based networks, challenges and open issues. Issue 6 (1st November 2017) - Sarigiannidis, Panagiotis; Lagkas, Thomas; Bibi, Stamatia; Ampatzoglou, Apostolos; Bellavista, Paolo
Abstract : The fifth‐generation (5G) mobile networks are expected to bring higher capacity, higher density of mobile devices, lower battery consumption and improved coverage. 5G entails the convergence of wireless and wired communications in a unified and efficient architecture. Mobile nodes, as defined in fourth‐generation era, are transformed in heterogeneous networks to make the front‐haul wireless domains flexible and intelligent. This work highlights a set of critical challenges in advancing 5G networks, fuelled by the utilisation of the network function virtualisation, the software defined radio and the software defined networks techniques. Furthermore, a novel conceptual model is presented in terms of control and management planes, where the inner architectural components are introduced in detail.